Contemporary applications of frontal sinus trephination: A systematic review of the literature. (17th February 2015) - Patel, Alpen B.; Cain, Rachel B.; Lal, Devyani
<x xml:space="preserve">Abstract</x> Our objective was to perform a systematic review of the literature on contemporary indications and outcomes for frontal sinus trephination and present an illustrative case of an endoscopically assisted repair of a subcutaneous frontal sinus fistula by trephination technique. PubMed and Ovid databases were used as data sources. A systematic review of the English literature was completed to review reports of frontal trephination from 1980 to 2014. Articles meeting inclusion criteria for inflammatory and noninflammatory indications were reviewed. Articles were systematically reviewed and graded by evidence‐based medicine level. An illustrative case from our institution is then presented. The systematic review identified 2, 621 published studies. Thirty‐eight studies were identified for inclusion. The indications, techniques, outcomes, safety, and complications were reviewed for noninflammatory and inflammatory conditions. There were 32 retrospective case series, reports, or cohort studies (level 4), four systematic reviews (level 3), one prospective analysis (level 3), and one meta‐analysis (level 2). Due to the heterogeneity of study cases and inclusion criteria, a meta‐analysis was not feasible. We also present a novel closure of an anterior skull base defect resulting in a subcutaneous fistula with use of a frontal trephination approach. The frontal sinus trephination should not be regarded as a procedure of the past, as it useful in the armamentarium of the modern sinus and skull base surgeon. This approach provides access for instrumentation for hard‐to‐reach frontal sinus disease either purely through a trephination approach or as a supplementation to the transnasal endoscopic approach. Evidence supporting frontal sinus trephination is of levels 2, 3, and 4. Level of Evidence NA Laryngoscope, 125:2046–2053, 2015